Principles of inorganic chemistry - Pfennig, Brian William (Hoboken: Wiley, 2021)
"This text is designed for undergraduates and introductory-level graduate students taking an inorganic or advanced inorganic chemistry course. It appeals to instructors looking for a more physical inorganic chemistry course. Written in an informal and engaging style, the author includes in-chapter worked problems, explains difficult concepts in simplistic terms, and deposits some mathematical derivations into "in-depth" boxes within the chapter or appendices. The largest change between this edition and the previous is a pedagogical restructuring of the material in a more logical order and the gradual development of underlying concepts as one progresses through the textbook. Several introductory chapters are streamlined and combined from the 1st edition, others are updated, and there is greater emphasis on molecular orbital depictions of organometallic transformations. New to this edition are an increased emphasis on the comparison of the strengths and weaknesses of different models, the interconnectedness of VBT (valence bond theory) and MOT (molecular orbital theory), and a more thorough discussion of the atoms in molecules topological model. In addition, there are more end-of-chapter problems and a solutions guide for adopting instructors"--
Includes bibliographical references and index.
Keywords: Chemistry, Inorganic -- Textbooks; Chemistry, Inorganic -- Study and teaching (Higher); Chemistry, Inorganic -- Study and teaching (Graduate)